Photonic Crystals – Optical Structures for Advanced Technology - Daniel Kacik; Ivan Martincek; Dusan Pudis; Norbert Tarjanyi; Ivan Turek (Communications - Scientific letters of the University of Zilina, 2008)
This paper presents experimental results in the field of photonic crystals investigation. There are presented our results of experimental investigation of one-dimensional photonic crystals appearing in nature, two-dimensional photonic crystals we formed in LiNbO3 and thin photoresist layers and results of our investigation of chromatic dispersion of photonic crystal fibers as well as the influence of fiber bending on their transmittance.